Structural Safety Assessment of Spread Footings in a Two-Story Hotel Project, Padang - Efrizon (CV. Get Press Indonesia, 2025)
Foundation design is a key factor in maintaining structural safety, particularly in seismic-prone regions such as Padang, Indonesia. This study evaluates the bearing capacity and stability of spread footings for a two-story reinforced concrete hotel based on superstructure load data and geotechnical parameters. According to Meyerhof’s theory, the designed footing—with a plan area of 1.8 × 1.8 m, a thickness of 0.5 m, and an embedment depth of 1.5 m—achieves an allowable bearing capacity of 127.14 kN/m², while the applied soil pressure is 110.50 kN/m². The pressure distribution (qmin = 120.30 kN/m²; qmax = 125.80 kN/m²) remains slightly below the allowable limit. The predicted settlement is 20 mm, which is within the 25 mm tolerance. Reinforcement detailing using D19 bars at 200 mm spacing provides adequate flexural and shear strength in accordance with SNI 2847:2019. These findings confirm that spread footings are a safe and economical foundation solution for low-rise buildings in Padang; however, further seismic evaluation is recommended to ensure long-term resilience.